KARAKTER MORFOLOGI BERAS SEBAGAI PEMBEDA VARIETAS PADI - Hanas, Dicky Frengky; Kriswiyanti, Eniek; Junitha, I Ketut (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2017)
This study aims to determine the morphological character of white, red and black rice as a differentiator of rice varieties. This research uses 10 rice samples which are 6 local rice of Kupang, 2 varieties of local superior rice and 2 Italian rice. The method used is direct observation of both qualitative and quantitative characteristics of rice. Long grain size of rice is a character that can indicate the distinguishing of local rice, domestic superior and rice from abroad. Character of rice morphology is a character very easily observed in knowing the difference of rice varieties. Character of rice morphology are easily characters observed in knowing the difference of rice varieties. Characters difference can be used to determine the adulteration of rice mixed.